F-MEEP: Fuzzy Logic Based Multihop Energy Efficient Routing Protocol for HWSN - Rizwan, Muhammad; Nisar, Muhammad S.; Jiang, Hongbo (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Energy preservation is one of the most important research challenges in Wireless Senor Networks (WSNs). In recent research, topologies and architectures have investigated that allow energy efficiency in WSNs. Clustering is one of the most famous energy efficient techniques. In clustering, the selection of cluster head (CH) and short distance multi-hop energy efficient communication between CH and base station (BS) plays a vital role in order to achieve the desired energy efficiency in the sensor network. In this energy saving solution, we purpose and combine the idea of fuzzy logic based CH selection and multihop short distance communication between CH and base station in order to prolong the stable period and life span of network. Our proposed routing protocol, Fuzzy Logic based Multihop Energy Efficient Routing Protocol (FMEEP) for Heterogeneous WSN, which uses fuzzy logic inference system (FIS) in order to select a qualified CH in the cluster formation process and minimizes the overall energy dissipation in the sensor network. The simulation results have shown that purposed routing scheme outperforms in terms of stability period and network lifetime as compared to previous routing protocols.Â 